# If x? 80 9X what is x

## Two solutions were found :

1.  x = -1/9 = -0.111
2.  x = 9

### Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

9*x-80-(9/x)=0

## Step  1  :

9 Simplify — x

#### Equation at the end of step  1  :

9 (9x - 80) - — = 0 x

## Step  2  :

#### Rewriting the whole as an Equivalent Fraction :

2.1   Subtracting a fraction from a whole

Rewrite the whole as a fraction using  x  as the denominator :

9x - 80 (9x - 80) • x 9x - 80 = ——————— = ————————————— 1 x

Equivalent fraction : The fraction thus generated looks different but has the same value as the whole

Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator

#### Adding fractions that have a common denominator :

2.2       Adding up the two equivalent fractions
Add the two equivalent fractions which now have a common denominator

Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:

(9x-80) • x - (9) 9x2 - 80x - 9 ————————————————— = ————————————— x x

#### Trying to factor by splitting the middle term

2.3     Factoring  9x2 - 80x - 9

The first term is,  9x2  its coefficient is  9 .
The middle term is,  -80x  its coefficient is  -80 .
The last term, "the constant", is  -9

Step-1 : Multiply the coefficient of the first term by the constant   9 • -9 = -81

Step-2 : Find two factors of  -81  whose sum equals the coefficient of the middle term, which is   -80 .

 -81 + 1 = -80 That's it

Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above,  -81  and  1
9x2 - 81x + 1x - 9

Step-4 : Add up the first 2 terms, pulling out like factors :
9x • (x-9)
Add up the last 2 terms, pulling out common factors :
1 • (x-9)
Step-5 : Add up the four terms of step 4 :
(9x+1)  •  (x-9)
Which is the desired factorization

#### Equation at the end of step  2  :

(x - 9) • (9x + 1) —————————————————— = 0 x

## Step  3  :

#### When a fraction equals zero :

3.1    When a fraction equals zero ...

Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.

Now,to get rid of the denominator, Tiger multiplys both sides of the equation by the denominator.

Here's how:

(x-9)•(9x+1) ———————————— • x = 0 • x x

Now, on the left hand side, the  x  cancels out the denominator, while, on the right hand side, zero times anything is still zero.

The equation now takes the shape :
(x-9)  •  (9x+1)  = 0

#### Theory - Roots of a product :

3.2    A product of several terms equals zero.

When a product of two or more terms equals zero, then at least one of the terms must be zero.

We shall now solve each term = 0 separately

In other words, we are going to solve as many equations as there are terms in the product

Any solution of term = 0 solves product = 0 as well.

#### Solving a Single Variable Equation :

3.3      Solve  :    x-9 = 0

Add  9  to both sides of the equation :
x = 9

#### Solving a Single Variable Equation :

3.4      Solve  :    9x+1 = 0

Subtract  1  from both sides of the equation :
9x = -1
Divide both sides of the equation by 9:
x = -1/9 = -0.111

### Supplement : Solving Quadratic Equation Directly

Solving  9x2-80x-9  = 0 directly

Earlier we factored this polynomial by splitting the middle term. let us now solve the equation by Completing The Square and by using the Quadratic Formula

#### Parabola, Finding the Vertex :

4.1      Find the Vertex of   y = 9x2-80x-9

Parabolas have a highest or a lowest point called the Vertex .   Our parabola opens up and accordingly has a lowest point (AKA absolute minimum) .   We know this even before plotting  "y"  because the coefficient of the first term, 9 , is positive (greater than zero).

Each parabola has a vertical line of symmetry that passes through its vertex. Because of this symmetry, the line of symmetry would, for example, pass through the midpoint of the two  x -intercepts (roots or solutions) of the parabola. That is, if the parabola has indeed two real solutions.

Parabolas can model many real life situations, such as the height above ground, of an object thrown upward, after some period of time. The vertex of the parabola can provide us with information, such as the maximum height that object, thrown upwards, can reach. For this reason we want to be able to find the coordinates of the vertex.

For any parabola,Ax2+Bx+C,the  x -coordinate of the vertex is given by  -B/(2A) . In our case the  x  coordinate is   4.4444

Plugging into the parabola formula   4.4444  for  x  we can calculate the  y -coordinate :
y = 9.0 * 4.44 * 4.44 - 80.0 * 4.44 - 9.0
or   y = -186.778

#### Parabola, Graphing Vertex and X-Intercepts :

Root plot for :  y = 9x2-80x-9
Axis of Symmetry (dashed)  {x}={ 4.44}
Vertex at  {x,y} = { 4.44,-186.78}
x -Intercepts (Roots) :
Root 1 at  {x,y} = {-0.11, 0.00}
Root 2 at  {x,y} = { 9.00, 0.00}

#### Solve Quadratic Equation by Completing The Square

4.2     Solving   9x2-80x-9 = 0 by Completing The Square .

Divide both sides of the equation by  9  to have 1 as the coefficient of the first term :
x2-(80/9)x-1 = 0

Add  1  to both side of the equation :
x2-(80/9)x = 1

Now the clever bit: Take the coefficient of  x , which is  80/9 , divide by two, giving  40/9 , and finally square it giving  1600/81

Add  1600/81  to both sides of the equation :
On the right hand side we have :
1  +  1600/81    or,  (1/1)+(1600/81)
The common denominator of the two fractions is  81   Adding  (81/81)+(1600/81)  gives  1681/81
So adding to both sides we finally get :
x2-(80/9)x+(1600/81) = 1681/81

Adding  1600/81  has completed the left hand side into a perfect square :
x2-(80/9)x+(1600/81)  =
(x-(40/9)) • (x-(40/9))  =
(x-(40/9))2
Things which are equal to the same thing are also equal to one another. Since
x2-(80/9)x+(1600/81) = 1681/81 and
x2-(80/9)x+(1600/81) = (x-(40/9))2
then, according to the law of transitivity,
(x-(40/9))2 = 1681/81

We'll refer to this Equation as  Eq. #4.2.1

The Square Root Principle says that When two things are equal, their square roots are equal.

Note that the square root of
(x-(40/9))2  is
(x-(40/9))2/2 =
(x-(40/9))1 =
x-(40/9)

Now, applying the Square Root Principle to  Eq. #4.2.1  we get:
x-(40/9) = √ 1681/81

Add  40/9  to both sides to obtain:
x = 40/9 + √ 1681/81

Since a square root has two values, one positive and the other negative
x2 - (80/9)x - 1 = 0
has two solutions:
x = 40/9 + √ 1681/81
or
x = 40/9 - √ 1681/81

Note that  √ 1681/81 can be written as
√ 1681  / √ 81   which is 41 / 9

4.3     Solving    9x2-80x-9 = 0 by the Quadratic Formula .

According to the Quadratic Formula,  x  , the solution for   Ax2+Bx+C  = 0  , where  A, B  and  C  are numbers, often called coefficients, is given by :

- B  ±  √ B2-4AC
x =   ————————
2A

In our case,  A   =     9
B   =   -80
C   =   -9

Accordingly,  B2  -  4AC   =
6400 - (-324) =
6724

80 ± √ 6724
x  =    ——————
18

Can  √ 6724 be simplified ?

Yes!   The prime factorization of  6724   is
2•2•41•41
To be able to remove something from under the radical, there have to be  2  instances of it (because we are taking a square i.e. second root).

√ 6724   =  √ 2•2•41•41  =2•41•√ 1   =
±  82 • √ 1   =
±  82

So now we are looking at:
x  =  ( 80 ± 82) / 18

Two real solutions:

x =(80+√6724)/18=(40+41)/9= 9.000

or:

x =(80-√6724)/18=(40-41)/9= -0.111

## Two solutions were found :

1.  x = -1/9 = -0.111
2.  x = 9

Processing ends successfully